Avalyn / Anastasia Linda Chaha Andrew Bakang … [et al.] - Andrew Bakang, Anastasia Linda Chaha; Akee, Alfonsa Alphonsus; Meliah, Anne; Lindang, Natalie; Aziz, Adrianna (Faculty of Computer and Mathematical Sciences, 2022)
Diet and exercise are components of a healthy lifestyle, and today we will examine how to improve and organize this lifestyle. To achieve this, one must accept responsibility for their behaviours and make sensible health decisions. The AVALYN idea comes into play here where it is designed for health enthusiasts and those who must maintain their health due to sickness. This app features a food sensor that can detect food quality, origin, and contamination level and identify if a meal is fresh, reheated, or contaminated. AVALYN, which signifies a beautiful breath of life in Old English, aids those suffering from food allergies. In addition, this application can be linked to smartwatches to monitor the user's hydration level through sensor scanning and provide health insights based on their health records. The AVALYN app is also particularly useful for drinkers because it detects and alerts the user to excessive alcohol consumption. Furthermore, using smartphone and smartwatch sensors, this application can monitor a user's body temperature and alert them if a fever is detected. The app's numerous useful functions can also remind users to take their medications on time and boost their hydration by monitoring their daily water intake. This app requires all personal information from users, as well as their medical history and preferred healthy lifestyle. With all its features in one application, AVALYN would assist busy people to monitor their health conditions most of the time, providing helpful alerts and reminders along the way if abnormalities were detected.